A determination of patient preferences for China online outpatient follow-up clinics by using discrete choice experiment: an exploratory study - Chen, Nan; Bai, Dan; Ning, Jing (Frontiers in Public Health, 2025)
ObjectiveInternet hospitals as a telehealth platform are rapidly growing in China both in quality and scale. This study aims to explore Chinese patients’ preferences, trade-offs and willingness to pay for attributes of online outpatient follow-up clinics.MethodsA discrete choice experiment was designed to elicit respondents’ stated preferences for six attributes. The online survey was conducted between November 2023 and December 2023, and mixed logit models were used to analyze the data.ResultsA total of 337 valid Chinese respondents were recruited. The results showed that an online outpatient follow-up clinic preferred by respondents could be described as low cost, provided by a tertiary Internet hospital, available same-day appointment, appointment with their own first diagnosing doctor, video appointment consultation, and payment by medical insurance. People with higher e-health literacy were more likely to accept an online outpatient follow-up appointment.ConclusionChinese respondents place a high value on waiting time for appointments, online payment methods, and continuity of online doctors. They were willing to pay more to avoid waiting a week for an online appointment. Our study provides valuable information for the telehealth policy-making and operation of Internet hospitals for healthcare sustainability.